The Functions of Silence in Confrontational Discourse - Melina Nikolić ([sic])
The present research attempts to highlight the functions of silence in confrontational discourse in television interviews within the framework of Critical Discourse Analysis (CDA) and Conversation Analysis (CA). The research starts with the hypothesis that silence can be used for expressing power in discourse. Since silence represents an element of discontinuity in speech, it occurs relatively rarely in confrontational discourse, which is characterized by continuous flow of speech and a quick turn-taking system. However, when it does occur, it is particularly obvious and can represent either an expression of power or absence of power. The research focuses on pauses and gaps, analyzes their functions of power, and is conducted as a contrastive analysis between English and Serbian. The results obtained show that both in the English and Serbian corpora, silence in confrontational discourse can indeed be a means for expressing power, but also a sign that the speaker is in an unfavourable position.